(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Hydrological modeling is an important aspect in watershed management. To process the hydrological models various types of hydrological, meteorological and tempo-spatial data is required. Those basin does not have the facility to record the data can use synthetic unit hydrograph method to simulate the parameters. In present work, SWAT (Soil & Water Assessment Tool) model was processed to parameterize the unit hydrograph for Kumbhi river basin in Kolhapur, India. The meteorological data was used from 2000-2014 to process the SWAT model. The outputs are validated with the help of SWAT-CUP tool using SUFI-II algorithm. It was observed that by K-fold method the peak discharge was 69.3 m3/sec, peak time was 4.9 hrs and base time is 14.32 hrs. The results obtained from SWAT model and those obtained from K-fold method shows good degree of fitness indicating the acceptance of model. The outcomes of this work will be helpful to researcher and policy makers to draw the hydrograph for Kumbhi basin and to plan the sustainable water resource management.